Walka Polek o emancypację – konteksty społeczno-kulturowe - Majka-Rostek, Dorota (Instytut Socjologii Uniwersytetu Wrocławskiego, 2019)
The article concerns selected socio-cultural contexts of the emancipation of Polish women as well as the question of them securing their right to vote. The text came into existence as a result of reflections from a seminar organised on May 24th, 2018, by the Department of the Sociology of Gender and Family, Institute of Sociology, University of Wrocław; the seminar was called “The Situation of Women in Democratic Poland: 100th Anniversary of Voting Rights”. The article includes the presentation and the development of some of the threads discussed during the seminar.
Keywords: emancipation; feminism; women’s voting rights